Β-Alanine Supplementation Attenuates the Neurophysiological Response in Animals Exposed to an Acute Heat Stress. (4th July 2022) - Belity, Tal; Hoffman, Jay R.; Horowitz, Michal; Epstein, Yoram; Bruchim, Yaron; Cohen, Hagit
Abstract: The effect of 30 days of β-alanine supplementation on neurophysiological responses of animals exposed to an acute heat stress (HS) was examined. Animals were randomized to one of three groups; exposed to HS (120 min at 40–41 °C) and fed a normal diet (EXP; n  = 12); EXP and supplemented with β-alanine (EXP + BA; n  = 10); or not exposed (CTL; n  = 10). Hippocampal (CA1, CA3 and DG) and hypothalamic (PVN) immunoreactive (ir) cell numbers of COX2, IBA-1, BDNF, NPY and HSP70 were analyzed. Three animals in EXP and one in EXP–BA did not survive the HS, however no significant difference ( p  = 0.146) was noted in survival rate in EXP + BA. The % change in rectal temperature was significantly lower ( p  = 0.04) in EXP + BA than EXP. Elevations ( p 's < 0.05) in COX-2, IBA-1 and HSP70 ir-cell numbers were noted in animals exposed to HS in all subregions. COX-2 ir-cell numbers were attenuated for EXP + BA in CA1 ( p  = 0.02) and PVN ( p  = 0.015) compared to EXP. No difference in COX-2 ir-cell numbers was noted between CTL and EXP + BA at CA1. BDNF-ir cell numbers in CA1, DG and PVN were reduced ( p 's < 0.05) during HS compared to CTL. No difference in BDNF-ir cell numbers was noted between EXP + BA and CTL in CA3 and PVN. NPY-ir density was reduced in exposed animals in all subregions, but NPY-ir density for EXP-BA was greater than EXP in CA3 ( p  < 0.001) and PVN ( p  = 0.04). β-Alanine supplementation attenuated the thermoregulatory and inflammatory responses and maintained neurotrophin and neuropeptide levels during acute HS. Further research is necessary to determine whether β-alanine supplementation can increase survival rate during a heat stress.